2010
DOI: 10.2174/1874210601004020084
|View full text |Cite
|
Sign up to set email alerts
|

From Systematic Reviews to Clinical Recommendations for Evidence- Based Health Care: Validation of Revised Assessment of Multiple Systematic Reviews (R-AMSTAR) for Grading of Clinical Relevance~!2009-10-24~!2009-10-03~!2010-07-16~!

Abstract: Research synthesis seeks to gather, examine and evaluate systematically research reports that converge toward answering a carefully crafted research question, which states the problem patient population, the intervention under consideration, and the clinical outcome of interest. The product of the process of systematically reviewing the research literature pertinent to the research question thusly stated is the “systematic review”.The objective and transparent approach of the systematic review aims to minimize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
81
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(82 citation statements)
references
References 11 publications
0
81
0
1
Order By: Relevance
“…44 l Quality of evidence included within systematic review: this reflects the rigour with which the reviews assessed the quality of the studies included in each of the reviews, looking for potential bias, conflicting results across individual studies, sparse evidence or a lack of relevance to the review question. 41 We used the Revised Assessment of Multiple Systematic Reviews (R-AMSTAR) quality appraisal tool to assess the methodological quality of all included systematic reviews 45 (see Appendix 15). Assessment of Multiple Systematic Reviews (AMSTAR) has good face and content validity but is unable to produce quantifiable assessments of quality.…”
Section: Meta-reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…44 l Quality of evidence included within systematic review: this reflects the rigour with which the reviews assessed the quality of the studies included in each of the reviews, looking for potential bias, conflicting results across individual studies, sparse evidence or a lack of relevance to the review question. 41 We used the Revised Assessment of Multiple Systematic Reviews (R-AMSTAR) quality appraisal tool to assess the methodological quality of all included systematic reviews 45 (see Appendix 15). Assessment of Multiple Systematic Reviews (AMSTAR) has good face and content validity but is unable to produce quantifiable assessments of quality.…”
Section: Meta-reviewsmentioning
confidence: 99%
“…46,47 R-AMSTAR is a revised version of the AMSTAR instrument which can quantify the quality of systematic reviews. 45 Due to the dearth of tools to assess quality of qualitative systematic reviews, we adapted the R-AMSTAR for this purpose (see Appendix 16). The qualitative tool was assessed out of 40 and papers were judged to be high quality if scored as ≥ 30 and low quality if scored < 30.…”
Section: Meta-reviewsmentioning
confidence: 99%
“…As part of this project we also searched for other systematic reviews covering the same topic published since 1 January 2011 with a revised AMSTAR score ≥32. 11 No such reviews were identified for hydrolysed formula.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Subgroup analysis suggested a significant difference in outcome according to study design or disease risk, with a more positive outcome in the single quasi-randomised controlled trial of normal risk infants. Analysis of data from randomised controlled trials for the most commonly studied partially hydrolysed formula (Nan HA/Good Start/Nidina HA/Beba HA, Nestlé, Vevey, Switzerland) showed no significant effect on risk of eczema at age 0-4 (0.94, 0.75 [5][6][7][8][9][10][11][12][13][14]. Direct comparison of extensively versus partially hydrolysed formula, and casein versus whey dominant extensively hydrolysed formula, did not show a significant difference in risk of eczema at age 0-4 or 5-14.…”
Section: Risk Of Eczemamentioning
confidence: 99%
See 1 more Smart Citation